Thematic Learning Model for Islamic Religious Education in Madrasah Ibtidaiyah - Ardinal, Eva; Destari, Dina; Irawan, Irawan; Zuhdi, Ahmad; Pranajaya, Syatria Adymas (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
During Mohammad Nuh's tenure as education minister in 2013, the KTSP 2006 curriculum was still in use. Because the 2006 KTSP was not in accordance with Law 20/2003 on National Education System, the education minister created a new curriculum, namely the 2013 curriculum. In this curriculum, the thematic learning model used for madrasah Ibtidaiyah emerged. This study aims to determine the thematic learning model of Islamic religious education in Madrasah Ibtidaiyah. The research method used is quantitative method, using a survey model that researchers use is google form and researchers also conduct in-depth interviews using WhatsApp. The results of the research that researchers found were that this thematic learning model was in accordance with the 2013 curriculum. The conclusion that researchers can draw from this research is that the thematic learning model of Islamic religious education is very helpful for students in the learning process at madrasah Ibtidaiyah. Limitations in thematic learning models include demanding relatively good learning abilities of students, both in academics and in the field of creativity, because thematic learning emphasizes students' ability to analyze. Therefore, the researcher hopes that future researchers can examine the thematic learning model of Islamic religious education at a more advanced level.